High glucose inhibits ClC-2 chloride channels and attenuates cell migration of rat keratinocytes - Pan F; Guo R; Cheng W; Chai L; Wang W; Cao C; Li S (Dove Medical Press, 2015)
Fuqiang Pan, Rui Guo, Wenguang Cheng, Linlin Chai, Wenping Wang, Chuan Cao, Shirong LiDepartment of Plastic and Reconstructive Surgery, Southwestern Hospital, Third Military Medical University, Chongqing, People’s Republic of China Background: Accumulating evidence has demonstrated that migration of keratinocytes is critical to wound epithelialization, and defects of this function result in chronic delayed-healing wounds in diabetes mellitus patients, and the migration has been proved to be associated with volume-activated chloride channels. The aim of the study is to investigate the effects of high glucose (HG, 25 mM) on ClC-2 chloride channels and cell migration of keratinocytes.Methods: Newborn Sprague Dawley rats were used to isolate and culture the keratinocyte in this study. Immunofluorescence assay, real-time polymerase chain reaction, and Western blot assay were used to examine the expression of ClC-2 protein or mRNA. Scratch wound assay was used to measure the migratory ability of keratinocytes. Transwell cell migration assay was used to measure the invasion and migration of keratinocytes. Recombinant lentivirus vectors were established and transducted to keratinocytes. Whole-cell patch clamp was used to perform the electrophysiological studies.Results: We found that the expression of ClC-2 was significantly inhibited when keratinocytes were exposed to a HG (25 mM) medium, accompanied by the decline of volume-activated Cl- current (ICl,vol), migration potential, and phosphorylated PI3K as compared to control group. When knockdown of ClC-2 by RNAi or pretreatment with wortmannin, similar results were observed, including ICl,vol and migration keratinocytes were inhibited.Conclusion: Our study proved that HG inhibited ClC-2 chloride channels and attenuated cell migration of rat keratinocytes via inhibiting PI3K signaling.Keywords: high glucose, keratinocytes, ClC-2, cell migration, PI3K